EDUCATIONAND LITERATURE THROUGH TRANSDISCIPLINARYPATHS - Fusaro, Marcia [UNESP] (Centro Univ Nove Julho, 2024)
This paper proposes some reflections on the importance of accessing literature as an educational process. From this perspective, it addresses transdisciplinary paths, especially with science, provided by the fact that literature fundamentally deals with the creative use of language and, in this sense, enables dialogic structures with other areas of knowledge. As an argumentative proposal, the example of literature as an educational instrument about science is mentioned. Authors from literature, education, science and also philosophy, such as Paulo Freire, Ubiratan D<acute accent>Ambrosio, Clarice Lispector, Ernesto Sabato, Gilles Deleuze and Mary Shelley, among others, are cited as reference examples on the topic. The intention is to contribute, in some way, to raising awareness, more urgent than ever, of understanding the importance of exercising literary reading in contemporary and future educational training.
Keywords: education and literature; literature and science; transdisciplinarity